2016
DOI: 10.1002/btpr.2367
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electrostatic interactions on the ultrafiltration behavior of charged bacterial capsular polysaccharides

Abstract: Charged polysaccharides are used in the food industry, as cosmetics, and as vaccines. The viscosity, thermodynamics, and hydrodynamic properties of these charged polysaccharides are known to be strongly dependent on the solution ionic strength because of both inter- and intramolecular electrostatic interactions. The goal of this work was to quantitatively describe the effect of these electrostatic interactions on the ultrafiltration behavior of several charged capsular polysaccharides obtained from Streptococc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
(55 reference statements)
1
8
0
Order By: Relevance
“…The selectivity values for the binary mixture are similar to those obtained with the pure components, suggesting that intermolecular interactions between the free and conjugated polysaccharides are relatively unimportant for the conditions examined in Figure . However, data obtained at higher polysaccharide/conjugate concentrations showed much lower selectivity at high filtrate flux due to fouling of the membrane (data not shown), consistent with results obtained previously for the pure polysaccharide (Hadidi et al, ).…”
Section: Results and Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…The selectivity values for the binary mixture are similar to those obtained with the pure components, suggesting that intermolecular interactions between the free and conjugated polysaccharides are relatively unimportant for the conditions examined in Figure . However, data obtained at higher polysaccharide/conjugate concentrations showed much lower selectivity at high filtrate flux due to fouling of the membrane (data not shown), consistent with results obtained previously for the pure polysaccharide (Hadidi et al, ).…”
Section: Results and Analysissupporting
confidence: 91%
“…Recent work by Hadidi, Buckley, and Zydney, (, ) and Emami, Motevalian, Pepin, and Zydney () have provided new insights into the factors controlling the ultrafiltration of pneumococcal polysaccharides, highlighting the important role of concentration polarization and fouling in determining the overall rate of polysaccharide transmission. In addition, Emami et al () showed that highly charged polysaccharides underwent elongation during tangential flow filtration (TFF), resulting in much greater fouling (and polysaccharide retention) in TFF cassettes compared with either stirred cell or hollow fiber modules.…”
Section: Introductionmentioning
confidence: 99%
“…Membrane fouling is commonly observed regardless of filter type and two main causes for the related decline in filter performance have been proposed . First, the adsorption of proteins onto a wide variety of membrane surfaces (caused by protein‐surface interaction) reduces the effective size of the membrane pores and causes caking on the membrane surface. Lim et al reported that membrane fouling caused by the formation of a dense and compact foulant layer on the membrane surface generated significant flux decline during the filtration of gelatin with an ultrafiltration membrane, especially at the gelatin isoelectric point .…”
Section: Introductionmentioning
confidence: 99%
“…The sterile final product was obtained with a 65% yield, obtaining 5–6 g/L HA and a molecular weight of about 4 × 10 6 Da. When dealing with the processing and recovery of molecules via membrane processes, an important aspect that must be studied is the relevant effect of electrostatic interactions between membrane materials and the solutes [ 49 , 50 , 51 ].…”
Section: Advances In Ha Bacterial Production Extraction and Purificationmentioning
confidence: 99%